2018
DOI: 10.1111/1365-2435.13097
|View full text |Cite
|
Sign up to set email alerts
|

A continental‐scale assessment of variability in leaf traits: Within species, across sites and between seasons

Abstract: Plant species show considerable leaf trait variability that should be accounted for in dynamic global vegetation models (DGVMs). In particular, differences in the acclimation of leaf traits during periods more and less favourable to growth have rarely been examined. We conducted a field study of leaf trait variation at seven sites spanning a range of climates and latitudes across the Australian continent; 80 native plant species were included. We measured key traits associated with leaf structure, chemistry an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 72 publications
0
27
0
Order By: Relevance
“…Such variability amongst co‐occurring species is to be expected (e.g. Bloomfield et al ., ) and likely reflects factors such as canopy position, and therefore light environment, and vapour pressure deficit. Our model performed less successfully when rates were normalized to the standard reference temperature of 25°C.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such variability amongst co‐occurring species is to be expected (e.g. Bloomfield et al ., ) and likely reflects factors such as canopy position, and therefore light environment, and vapour pressure deficit. Our model performed less successfully when rates were normalized to the standard reference temperature of 25°C.…”
Section: Discussionmentioning
confidence: 99%
“…This is a subset (combined here with carbon isotope analysis) of a larger dataset presented in Bloomfield et al . (). At each visit, we chose young, fully developed leaves from two sun‐exposed branches.…”
Section: Methodsmentioning
confidence: 97%
“…Second, there is a critical temporal scale mismatch. Co-existing species in a plant community can have different phenologies, plus the traits themselves may vary over the seasons [33][34][35] (Figure 1). As such, not only trait values for each species, but also their community means, should vary across seasons ( Figure 1).…”
Section: Do Satellites "See" the Same Fd As Field Ecologists?mentioning
confidence: 99%
“…Furthermore, a field study of boreal and temperate tree species experiencing an artificial change in growth temperature revealed that acclimation eliminated 80% of the expected increase in leaf respiration rates as a result of a 3.4°C increase in temperature (Reich et al ., ). The existence of seasonal thermal acclimation of leaf dark respiration is also supported by measurements of field‐grown deciduous and evergreen species in a variety of ecosystems (Zaragoza‐Castells et al ., ; Bloomfield et al ., ). Therefore, it may be that one aspect of acclimation is to reduce capacity limitations when they occur (e.g.…”
Section: Principle 4 – Plant Respiratory Acclimation Involves Adjustmmentioning
confidence: 97%